Experiences of siblings of children with chronic diseases revealed by the dramatic therapeutic play - Marcela Astolphi Souza; Edmara Bazoni Soares Maia; Circéa Amália Ribeiro; Luciana de Lione Melo (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective To understand, through dramatic therapeutic play, the experiences of siblings of children with chronic diseases. Method Phenomenological study, in the light of Heideggerian philosophical framework, conducted with 12 siblings of children with chronic diseases, aged between three and 11 years, accompanied in a public teaching hospital in the countryside of the state of São Paulo. The phenomenological interviews were audio-recorded and mediated by sessions of dramatic therapeutic play; later, interpreted from the Heideggerianphilosophical framework and thematic literature. Results The siblings demonstrated that they are affectively touched in the mode of sadness, longing and affection towards the sick child and, by the daily occupations imposed by the disease. Conclusion The dramatic therapeutic play enabled the siblings of children with chronic diseases to expose their experiences permeated by the limitations of the child's chronic disease. Instituting actions for the inclusion of the sibling during the nursing care of the child with chronic disease is urgent to improve its quality.